PENINGKATAN KEAKTIFAN BELAJAR SISWA MELALUI PROJECT BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA - prastio rohi apriatna suwardi; Sarah Safinatunnajah; Roni Rustandi (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
Student learning activeness is an important indicator of successful learning. However, preliminary observations in Pancasila Education learning in class XI-3 of SMAN 2 Tangerang Selatan indicated that student participation was still relatively low. Students rarely asked questions, expressed opinions, participated in discussions, or collaborated actively during learning activities. This study aimed to improve student learning activeness through the implementation of the Project Based Learning (PjBL) model. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages. The subjects of the study were 40 students of class XI-3 SMAN 2 Tangerang Selatan. Data were collected through observation, interviews, and documentation. The findings revealed a significant improvement in students’ learning activeness across cycles. The percentage of learning activeness increased from 37.5% in the pre-cycle stage to 59.3% in Cycle I and reached 84.3% in Cycle II. These findings indicate that the implementation of Project Based Learning effectively improves students’ learning activeness in Pancasila Education. Therefore, PjBL can be used as an effective learning model to enhance student engagement during the learning process.